2019
DOI: 10.1097/md.0000000000016338
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus nonsurgical treatment of primary acute patellar dislocation

Abstract: Background: To systematically review the efficacy of surgical versus nonsurgical treatment for acute patellar dislocation. Materials and Methods: PubMed, Cochrane, and Embase were searched up to February 12, 2019. After removing duplicates, preliminary screening, and reading the full texts, we finally selected 16 articles, including 11 randomized controlled trials and 5 cohort studies. The quality of the enrolled studies was evaluated by Jadad score or Newcastle–Ottawa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Portanto, novos ensaios clínicos randomizados de melhor qualidade metodológica foram recomendados. A ►Tabela 1- 4,8,26,35,36 mostra os resultados das revisões sistemáticas com metanálise comparando o tratamento conservador ao cirúrgico para luxação primária da patela.…”
Section: Tratamentounclassified
See 1 more Smart Citation
“…Portanto, novos ensaios clínicos randomizados de melhor qualidade metodológica foram recomendados. A ►Tabela 1- 4,8,26,35,36 mostra os resultados das revisões sistemáticas com metanálise comparando o tratamento conservador ao cirúrgico para luxação primária da patela.…”
Section: Tratamentounclassified
“…Therefore, new randomized clinical trials of better methodological quality have been recommended. ►Table 1-4, 8,26,35,36 shows the results of systematic reviews with meta-analysis comparing conservative with surgical treatment for primary patellar dislocation.…”
Section: Treatment Conservative Treatmentmentioning
confidence: 99%
“…Non-weight-bearing status can typically be discontinued as tolerated by the patient. Controversy exists on surgical versus conservative management on primary traumatic patellar dislocation [32]; however, it is reasonable to begin with nonoperative management. Palpable defects of the parapatellar ligament structures, recurrent subluxation on initial examination, and findings of osteochondral lesion on imaging are indications for referral to orthopedic surgery.…”
Section: Managementmentioning
confidence: 99%
“…At present, however, consensus on the best treatment recommendations and guidelines for primary patellar dislocation is lacking [ 47 ]. A recent meta-analysis by Yang et al comprising 16 randomised controlled trials (RCT) or cohort studies published between 1986 and 2018 cautiously concluded that surgical treatment might also be more favourable than conservative treatment for patients with their first patellar dislocation [ 53 ]. This conclusion was based on the finding that surgically treated patients had higher Kujala scores (anterior knee-specific patient-reported outcomes) and a lower rate of re-dislocations compared with conservatively treated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the rapid development of surgical techniques during the past few decades, the conclusion was based on heterogenous study populations. Previous results have indicated that not all surgical techniques are as equally effective [ 2 , 5 , 46 , 50 , 53 ].…”
Section: Introductionmentioning
confidence: 99%